2018
DOI: 10.1002/cssc.201800826
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Interfaces of Superadsorbing Graphene‐Based Electrodes with Gas and Electrolyte to Boost Gas Evolution and Activation Reactions

Abstract: Electrochemical gas evolution and activation reactions are complicated processes, involving not only active electrocatalysts but also the interaction among solid electrodes, electrolyte, and gas-phase products and reactants. In this study, multiphase interfaces of superadsorbing graphene-based electrodes were controlled without changing the active centers to significantly facilitate mass diffusion kinetics for superior performance. The achieved in-depth understanding of how to regulate the interfacial properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…It is well recognized that the properties of supports play key roles in regulating the hydrogenation reactivity, e.g., by metal–support interaction, which governs the dispersion and electronic structures of metal species. Several studies have indicated that carbon materials are more efficient supports for selective hydrogenation than traditional oxides, including Al 2 O 3 and SiO 2 . ,, This phenomenon is due to their unique chemical versatility, such as tunable acidity, basicity, surface chemistry, and affinity to different solvents. In particular, two-dimensional (2D) carbons have been considered to be the leading carbon support, as they have large accessible sites that favor reactant–product mass transportation. The existence of giant π structures promotes absorption ability with various reactants, particularly for aromatic substrates. On the other hand, the engineering of the nanocarbons through substitutional doping can effectively alter both the chemical and electronic properties as well as the chemisorption energy of different molecules, thus altering the catalytic reaction mechanisms, potentially leading to significant activity enhancement. , The interest in doped carbons thus stems from the tunability of properties by compositional variation. For example, doping positively polarized atoms may facilitate the adsorption and dissociation of O 2 molecules via bridging (promoting) the electron transfers from graphitic carbon to oxygen, which may improve the catalytic activity of nanocarbon in electrochemical reactions. Nitrogen and sulfur have been widely used as electron donors to change the π-conjugated system at the periphery of carbon structures. This approach generates more defects and anchoring sites for metal particles and strengthens the interaction between metal particles and carbon supports, thereby benefiting the transfer of electrons from supports to metal catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…It is well recognized that the properties of supports play key roles in regulating the hydrogenation reactivity, e.g., by metal–support interaction, which governs the dispersion and electronic structures of metal species. Several studies have indicated that carbon materials are more efficient supports for selective hydrogenation than traditional oxides, including Al 2 O 3 and SiO 2 . ,, This phenomenon is due to their unique chemical versatility, such as tunable acidity, basicity, surface chemistry, and affinity to different solvents. In particular, two-dimensional (2D) carbons have been considered to be the leading carbon support, as they have large accessible sites that favor reactant–product mass transportation. The existence of giant π structures promotes absorption ability with various reactants, particularly for aromatic substrates. On the other hand, the engineering of the nanocarbons through substitutional doping can effectively alter both the chemical and electronic properties as well as the chemisorption energy of different molecules, thus altering the catalytic reaction mechanisms, potentially leading to significant activity enhancement. , The interest in doped carbons thus stems from the tunability of properties by compositional variation. For example, doping positively polarized atoms may facilitate the adsorption and dissociation of O 2 molecules via bridging (promoting) the electron transfers from graphitic carbon to oxygen, which may improve the catalytic activity of nanocarbon in electrochemical reactions. Nitrogen and sulfur have been widely used as electron donors to change the π-conjugated system at the periphery of carbon structures. This approach generates more defects and anchoring sites for metal particles and strengthens the interaction between metal particles and carbon supports, thereby benefiting the transfer of electrons from supports to metal catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally,t he interfacial static potential between the Co nanoparticles and the support could also be applied generally for the selective HDO of vanillin, substituted vanillin, and isomers of vanillinw ith electron-donating groups (ÀOH or NH 2 )a t the ortho or para position, which include 2-hydroxy-3-methoxybenzaldehyde, 3-methoxy-4-aminobenzaldehyde, 2-hydroxybenzaldehyde, and 4-hydroxybenzaldehyde (Table S5), with an excellent tolerance of different functionalgroups. [32,33] To further investigate the role of the 3D architecture of Co/ NG/CF catalysts, we monitored the selectivity of vanillin hydrogenolysis over as eries of Co/NG/CF-y catalystsw ith similarC o contents( Ta ble S1) but increased contents of N-doped gra- (Figure 5a-d). To avoid the competitive adsorption of reactants and products to ensure the diffusion-controlled rate of the encounter of the substrates and intermediates, ab etter dispersion of the active centers was further achievedb yi ncreasingt he exposed surface area inside the 3D frameworks.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, 3‐hydroxy‐4‐methoxybenzaldehyde with a meta −OH group could only increase the electron density of the adsorbed functional group slightly and offers a much lower selectivity (15 %) towards 2‐hydroxy‐3‐metoxytoluene. Additionally, the interfacial static potential between the Co nanoparticles and the support could also be applied generally for the selective HDO of vanillin, substituted vanillin, and isomers of vanillin with electron‐donating groups (−OH or NH 2 ) at the ortho or para position, which include 2‐hydroxy‐3‐methoxybenzaldehyde, 3‐methoxy‐4‐aminobenzaldehyde, 2‐hydroxybenzaldehyde, and 4‐hydroxybenzaldehyde (Table S5), with an excellent tolerance of different functional groups …”
Section: Resultsmentioning
confidence: 99%
“…(3) The electrochemical surface area of the Ti@Ni 0.85 Se‐THA electrode was very high compared with Ti@Ni 0.85 Se‐NSA, which was responsible for the increased number of active sites . (4) The in situ direct growth of the Ni 0.85 Se triple hierarchy architecture on the Ti mesh helps to provide efficient conductive pathways that can expedite the electrode kinetics, decrease the charge‐transfer resistance, and facilitate mass transfer of the electrolyte and release of generated gas bubbles …”
Section: Resultsmentioning
confidence: 99%